2010
DOI: 10.1186/ar3013
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and synovial fluid microRNAs as potential biomarkers of rheumatoid arthritis and osteoarthritis

Abstract: IntroductionMicroRNAs (miRNAs), endogenous small noncoding RNAs regulating the activities of target mRNAs and cellular processes, are present in human plasma in a stable form. In this study, we investigated whether miRNAs are also stably present in synovial fluids and whether plasma and synovial fluid miRNAs could be biomarkers of rheumatoid arthritis (RA) and osteoarthritis (OA).MethodsWe measured concentrations of miR-16, miR-132, miR-146a, miR-155 and miR-223 in synovial fluid from patients with RA and OA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
394
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(414 citation statements)
references
References 40 publications
13
394
3
4
Order By: Relevance
“…Recent studies have revealed that miR‐146 is primarily involved in the regulation of inflammation and other processes that function in the innate immune system (Sonkoly, Stahle & Pivarcsi, 2008). miR‐146a has been shown to be a circulating miRNA that is increased in synovial tissues and fibroblasts in rheumatoid arthritis (RA) patients as a particularly important negative regulator of nuclear factor‐κB (NF‐κB) signaling (Murata et al., 2010; Stanczyk et al., 2008; Taganov, Boldin, Chang & Baltimore, 2006). miR‐146a has also received much attention in the field of OA research.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that miR‐146 is primarily involved in the regulation of inflammation and other processes that function in the innate immune system (Sonkoly, Stahle & Pivarcsi, 2008). miR‐146a has been shown to be a circulating miRNA that is increased in synovial tissues and fibroblasts in rheumatoid arthritis (RA) patients as a particularly important negative regulator of nuclear factor‐κB (NF‐κB) signaling (Murata et al., 2010; Stanczyk et al., 2008; Taganov, Boldin, Chang & Baltimore, 2006). miR‐146a has also received much attention in the field of OA research.…”
Section: Introductionmentioning
confidence: 99%
“…The role of miR-132 in inflammation and autoimmunity is not well established. MiR-132 is differentially expressed in different tissues and in the synovial fluid from rheumatoid arthritis patients [16,17]. However, no further studies have investigated the importance of these miRNA to autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…In culture, RA fibroblast like synoviocytes (FLS) proliferate and secrete a variety of cytokines/ chemokines/angiogenic factors, including fibroblast growth factor, granulocytemacrophage colony stimulating factor, interleukin 6 (IL-6), IL-8, monocyte chemoattractant protein 1 (MCP-1) and macrophage inflammatory proteins 1 , and they present various adhesion molecules on their surfaces. Since the first report by Stanczyk et al in 2008, several reports have described the altered miRNAs in the joint and/or peripheral blood leucocytes of patients with RA, including miR-155, miR-146 and others (Table 1) ( Stanczyk, et al, 2008;Nakasa, et al, 2008;Pauley, et al, 2008;Murata, et al, 2010;Li, et al, 2010;Fulci, et al, 2010;Nakamachi, et al, 2009. Niimoto, et al, 2010.…”
Section: Mirna and Rheumatoid Arthritismentioning
confidence: 99%